Exploring Pedagogical Communication Patterns in German Language Teaching at the University Level - Nurming Saleh; Nursalam Nursalam; Agung Rinaldy Malik (Journal of Innovative and Creativity, 2025)
This study investigates the communication patterns employed by lecturers in teaching German language competencies at the university level. Focusing on the four core skills; reading (Lesen), listening (Hören), writing (Schreiben), and speaking (Sprechen), the research was conducted in the German Language Education Study Program, Faculty of Language and Literature, during the even semester of the 2020/2021 academic year. The participants included all students from Class A in the fourth semester and their lecturers. Data were collected using observations, interviews, and documentation, and analyzed through Miles and Huberman’s interactive model, comprising data collection, data reduction, data display, and conclusion drawing. The findings revealed a total of 291 communication patterns, categorized as follows: primary (31%), secondary (24%), circular (21%), linear (17%), and interpersonal (7%). Among these, primary communication patterns—both verbal and nonverbal—were the most frequently used. The study highlights the strategic role of diverse communication approaches in fostering effective German language instruction, emphasizing the need for lecturers to integrate varied patterns to enhance student engagement and comprehension.